An Analysis of Economic Wealth of God’s People from Nomadic to Post Exilic Era - Halim Wiryadinata (Sekolah Tinggi Teologi Intheos Surakarta, 2019)
The terminology of the economic wealth is not actually related to the poor in terms of poverty and wealth in the Bible. The terminology of wealth and poverty is not a matter of relationship to the business or economy, but they are rather to have relationships to seek the righteousness of God. Thus, one should clarify the meaning of wealth and poverty in order to seek the real meaning of the Old Testament theology. The eras of Nomadic to Post Exilic give the idea of how God dealt with the people of God in term of sinful nature. It is not the matter of the economic situation, but it is blessedness for the people who seek Him with all their heart. Nomadic era gives an idea of how God gives the promise land to the people of Israel as long as they can keep the covenant. However, throughout the history the Israelites never entered into the promise land, except Caleb and Joshua. The picture of Babylonia is the wrath of God to the people of Israel who never listen to the command of God. In conclusion, seeking God with full heart will find ‘rest’ forever and keep the promise forever more. Keeping the righteousness of God will bring justice to the poor and let the poverty be away from the poor.